Impact of alcohol consumption on the mineral composition of the body in the rat (Revista Española de Fisiología, 1984)
The influence of consumption of increasing ethanol solutions of 5, 7.5 and 10%/99.5% (v/v), on total body mineral composition, but particularly the ethanol effect on the contents of Ca, P, Mg, Zn, Na and K, for eight weeks was studied in the adult rat.Both females and males voluntarily lower their liquid intake when daily ethanol ingestion is about 1.4 and 1.7 g, respectively.These ethyl ingestions introduce some modifications in male body composition, but not in females, with an increase in the relative water content and a decrease of the carcass dry substance.The latter would be the main reason for the decrease in male body content of Ca, P, Zn, Mg and K, at least from the 7.5% v/v solution.Ca, P and Zn seem to be the most modified elements.Likewise, there are negative influences regarding Na, but they are not clearly evidenced until ethanol consumption reaches 1.9 g per day.Female body weight did not undergo any change, under any tested experimental conditions or their body ashes suffer any deterioration.